2021
DOI: 10.1002/anie.202102701
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Highly Efficient Synthesis and Selective Methylation of C(sp3)‐Bridged [6]Cycloparaphenylenes from Fluoren[3]arenes

Abstract: An approach to the highly efficient synthesis of C(sp3)-bridged [6]cycloparaphenylenes (C[6]CPPs)f rom fluoren[3]arenes (F[3]As)w as developed. Consequently, F[3]As as anew kind of macrocyclic arenes were synthesized. Followed by the demethylation, triflation and intramolecular aryl-aryl coupling reactions, C[6]CPPs were then conveniently obtained. Interestingly, C[6]CPPs could be selectively methylated to produce their fully outer-methyl-substituted derivatives.T he crystal structures showed the hydroxyl-subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
0
38
1
Order By: Relevance
“…Themain interactions in the packing mode of C[6]CPP5 were .Hydrogen atoms are omitted for clarity. [39] Angewandte Chemie Forschungsartikel found to be the intermolecular C(sp 3 )-H•••p interactions between the adjacent molecules of C [6]CPP5 with the distances of 2.829 and 2.880 ,a nd the intermolecular C(sp 2 )-H•••p interaction with an average distance of 2.834 (Figure S90).…”
Section: Selective Methylation Of C[6]cppsmentioning
confidence: 99%
See 4 more Smart Citations
“…Themain interactions in the packing mode of C[6]CPP5 were .Hydrogen atoms are omitted for clarity. [39] Angewandte Chemie Forschungsartikel found to be the intermolecular C(sp 3 )-H•••p interactions between the adjacent molecules of C [6]CPP5 with the distances of 2.829 and 2.880 ,a nd the intermolecular C(sp 2 )-H•••p interaction with an average distance of 2.834 (Figure S90).…”
Section: Selective Methylation Of C[6]cppsmentioning
confidence: 99%
“…However,itwas surprisingly found that if am ixture solvents of C 6 D 6 and Hydrogen atoms not involved in the non-covalent interactions were omitted for clarity. [39] Tabelle 1: The Optimization of aryl-aryl coupling reaction from 2,7-OTf- S51), in which one singlet at 7.73 ppm belonged to the aromatic proton, while the inner and outer protons of the methylene groups showed two doublets at 4.15 and 3.83 ppm, respectively.T his result also indicated its high D 3d symmetric structure.Moreover,the red crystal of C [6]CPP1 could be obtained by slow diffusion of methanol into aC H 2 Cl 2 solution of C [6]CPP1 at room temperature.T he crystal structure showed C [6]CPP1 had ac ylindrical shape-like structure with an average diameter and cavity depth 7.766 and 3.971 ,r espectively,a nd an average CÀCsingle bond that connected the phenylene units was 1.475 ,w hich were all consistent with those of the Itamisreport. [22] Since C[6]CPP2 showed good solubility in benzene,i ts 1 HNMR spectrum in C 6 D 6 was then performed.…”
Section: Synthesis and Structures Of C[6]cppsmentioning
confidence: 99%
See 3 more Smart Citations